2004
DOI: 10.1590/s0036-46652004000600005
|View full text |Cite
|
Sign up to set email alerts
|

Enzootic transmission of Trypanosoma cruzi and T. rangeli in the Federal District of Brazil

Abstract: SUMMARYThe Federal District of Brazil (DF) lies within the Cerrado biome, where open shrubland (savannas) is interspersed with riverside gallery forests and permanent swamps (veredas). Trypanosoma cruzi-infected native triatomines occur in the area, but the enzootic transmission of trypanosomatids remains poorly characterized. A parasitological survey involving sylvatic triatomines (166 Rhodnius neglectus collected from Mauritia flexuosa palms) and small mammals (98 marsupials and 70 rodents, totaling 18 speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 35 publications
1
10
1
8
Order By: Relevance
“…Rhodnius neglectus is widespread in central Brazil and has an important role in enzootic transmission of T. cruzi 5,7 . Apart from the invasion of adults in domiciles 48 , there is evidence of household infestation of R. neglectus (with bugs occasionally establishing breeding colonies) in the States of Minas Gerais, Goiás, and São Paulo 18,49,50 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rhodnius neglectus is widespread in central Brazil and has an important role in enzootic transmission of T. cruzi 5,7 . Apart from the invasion of adults in domiciles 48 , there is evidence of household infestation of R. neglectus (with bugs occasionally establishing breeding colonies) in the States of Minas Gerais, Goiás, and São Paulo 18,49,50 .…”
Section: Discussionmentioning
confidence: 99%
“…), which are frequently infected with T. cruzi, thus justifying high infection indices when compared with other species of triatomines 26,28,29 . A study on T. cruzi reservoirs in DF showed that specimens of D. albiventris are responsible for maintaining enzootic circulation of the parasite in the region, where 33% of these mammals were infected 5 . However, P. megistus has varied feeding habits, also feeding on birds, dogs, cats, rodents, cattle, goats, pigs, and humans 17,27,30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R. neglectus é uma espécie característica do cerrado no Brasil central com um papel importante na transmissão enzoótica de Trypanosoma cruzi e T. rangeli 6 . Além da invasão de adultos nos domicílios 7 , existem evidências de formação de colônias domiciliares de R. neglectus nos Estados de Minas Gerais, São Paulo e Goiás [8][9][10] , sendo considerado como um vetor secundário na transmissão da doença de Chagas.…”
Section: Rhodnius Neglectusunclassified
“…Thaís Tâmara Castro Minuzzi-Souza [1] , Nadjar Nitz [2] , César Augusto Cuba Cuba [1] , Marcelo Santalucia [3] , Monique Knox [4] , Luciana Hagström [2] , Camilla Bernardes Furtado [1] , Tamires Emanuele Vital [2] , Marcos Takashi Obara [1] , Mariana Machado Hecht [2] and Rodrigo Gurgel-Gonçalves 5,6 .…”
Section: Synanthropic Triatomines As Potential Vectors Of Trypanosomamentioning
confidence: 99%